Clinical Characteristics and Risk Factors for Mortality in Cryptococcal Meningitis: Evidence From a Cohort Study - Wang, Fengjuan; Wang, Yu; He, Jianqing; Cheng, Zhe; Wu, Shouquan; Wang, Minggui; Niu, Ting (Frontiers in Neurology, 2022)
Introduction: Despite advances in the diagnosis and management, cryptococcal meningitis (CM) is still associated with high mortality due to insufficient knowledge about clinical characteristics and risk factors for poor outcomes. The aim of the present study is to provide additional evidence for regarding clinical characteristics, diagnosis, and factors associated with increased risk of mortality in CM patients. Methods: In this cohort study, we included eligible patients consecutively admitted to West China Hospital between January 2009 and December 2018. The clinical characteristics and diagnosis method of cerebrospinal fluid culture and India ink stain were analyzed. Independent risk factors were identified by a multivariable logistic regression. Results: A total of 186 CM patients were included in the analysis. After a one-year follow-up, 63 patients had died. Headache is the most common presenting symptom (97.3%), followed by vomiting (72%), fever (71.5%), altered consciousness (45.7%), abnormal vision (32.8%), and seizure (15.1%). Older age, altered consciousness or seizures, lower white blood cell count or total protein in cerebrospinal fluid (CSF), and unidentified CSF cryptococcal antigen (CrAg) are all factors associated with increasing risk of death (P < 0.05). We also found a dose-dependent trend between the number of symptoms and risk of death (trend p < 0.001). Multivariate logistic regression revealed that age (P = 0.004, OR = 1.042, 95% CI 1.013-1.071), seizure (P = 0.025, OR = 3.105, 95% CI 1.152-8.369), altered consciousness (P < 0.001, OR=6.858, 95% CI 3.063-15.38), and unidentified CSF CrAg are the independent prognostic factors. In addition, we observed that diagnosis of 28.5% and 22.5% CM could not be established by a single testing of CSF India ink stain or culture, respectively. Use of multiple testing methods or combination of the two assays increases the detection rate. Conclusion: Our data show that older age, seizures, altered consciousness, and an inability to detect CSF CrAg are the independent risk factors of death within one year in CM patients. Moreover, we recommend use of multiple testing methods with CSF culture and India ink stain. Combined testing with both assays should be considered for initial CM diagnosis.